Bridging Linguistic Divides: Undergraduate Experiences of Code-Switching in English Language Learning Environments in Pakistan - Nawaz, Muhammad Haseeb; Yali, Zhu; Hameed, Saba (Pakistan Languages and Humanities Review, 2023)
The study’s objective was to learn more about how instructors see code-switching in the context of teaching English as a foreign language. To do this, they used a descriptive survey and interview approach to examine the tasks and outcomes of code-switching. In order to learn more about code-switching functions and their impacts in the classroom, 46 participants answered a questionnaire. The present study explored the students’ Undergraduate Experiences of Code-Switching in English Language Learning Environments in Pakistan. A Quantitative method was used for the study and a survey research design was employed to collect information from participants. A convenience sampling technique was used on a sample of 300 students (158 female, 142 male) taken from the university students. The findings of the study also revealed that students’ perceptions of code-switching had a negative impact on learners’ academic achievements, as they believe that switching from English to Urdu breaks their concentration in the classroom. The results of the study indicated that most students in the BS English program believe that code-switching hinders the development of English language proficiency in the classroom. It is recommended that code-switching should not be objective-based and context-based because it effects the development of English language learning on students.